Manajemen Pakan Ternak Sapi Potong di Kandang Percobaan Program Studi Peternakan Fakultas Pertanian - Afridayanti, Neny; Nurhayani, Nurhayani; Junita, Armi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Afridayanti N, Nurhayani N, Junita A. 2022. Feed management of beef cattle in the experimental cage of animal husbandry study program faculty of agriculture. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 1000-1010. Palembang: Penerbit dan Percetakan Universitas Sriwijaya (UNSRI).The purposes of this study were to identify and study animal feed management in the Experimental Cage, Department of Animal Technology and Industry, Animal Husbandry Study Program, Universitas Sriwijaya. The method used is a survey method consisting of primary and secondary data. Primary data obtained directly in the field through direct interviews with respondents in this case are the head of the cage and the staff of the cage, while secondary data were obtained from related institutions, namely the Department of Animal Technology and Industry, Animal Husbandry Study Program, Universitas Sriwijaya and livestock environmental conditions. The data obtained are then processed and presented in the form of descriptions and pictures. This observations be discovered that the beef cattle rearing system using a semi-intensive maintenance system and the management of feeding beef cattle in experimental cages is quite good but for the provision of concentrate feed it is still less visible than the percentage of body weight of cattle which is on average less than 2% while for feeding forage only relies on forage around the experimental enclosure.